2021
DOI: 10.1021/acsami.1c15875
|View full text |Cite
|
Sign up to set email alerts
|

Wake-up Free Ferroelectric Rhombohedral Phase in Epitaxially Strained ZrO2 Thin Films

Abstract: Zirconia- and hafnia-based thin films have attracted tremendous attention in the past decade because of their unexpected ferroelectric behavior at the nanoscale, which enables the downscaling of ferroelectric devices. The present work reports an unprecedented ferroelectric rhombohedral phase of ZrO2 that can be achieved in thin films grown directly on (111)-Nb:SrTiO3 substrates by ion-beam sputtering. Structural and ferroelectric characterizations reveal (111)-oriented ZrO2 films under epitaxial compressive st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
54
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 38 publications
6
54
1
Order By: Relevance
“…Since ferroelectric Si-doped HfO 2 and Hf 1– x Zr x O 2 (HZO) thin films have been discovered, they have attracted abundant interest due to their remarkable ferroelectricity and excellent compatibility with the complementary metal–oxide–semiconductor process, , leading to new developments in future and emerging non-volatile memory technologies. Even though there are a few reports of rhombohedral polar phases in epitaxial films, the origin of ferroelectricity in HfO 2 -based polycrystalline thin films is mostly reported to be due to a non-centrosymmetric Pbc 2 1 orthorhombic (o) phase. ,, A paraelectric P 2 1 / c monoclinic (m) phase is the major phase in bulk fluorite HfO 2 and ZrO 2 ceramics at room temperature . In pure HfO 2 thin films, the m-phase is the primary phase, which results in paraelectric film properties. , As a component in the HZO system, undoped ZrO 2 thin films have been investigated less intensely due to the loss of ferroelectric properties at thicknesses of 10 nm .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ferroelectric Si-doped HfO 2 and Hf 1– x Zr x O 2 (HZO) thin films have been discovered, they have attracted abundant interest due to their remarkable ferroelectricity and excellent compatibility with the complementary metal–oxide–semiconductor process, , leading to new developments in future and emerging non-volatile memory technologies. Even though there are a few reports of rhombohedral polar phases in epitaxial films, the origin of ferroelectricity in HfO 2 -based polycrystalline thin films is mostly reported to be due to a non-centrosymmetric Pbc 2 1 orthorhombic (o) phase. ,, A paraelectric P 2 1 / c monoclinic (m) phase is the major phase in bulk fluorite HfO 2 and ZrO 2 ceramics at room temperature . In pure HfO 2 thin films, the m-phase is the primary phase, which results in paraelectric film properties. , As a component in the HZO system, undoped ZrO 2 thin films have been investigated less intensely due to the loss of ferroelectric properties at thicknesses of 10 nm .…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the formation of the o- and the t-phase in thin ZrO 2 films seems to depend on different factors. For instance, electrode materials , and interface layers can play a role, but stress and strain can favor the o-phase too. In contrast, crystallization in the m-phase is often observed for atomic layer deposited (ALD)-doped HfO 2 or mixed Hf x Zr 1– x O 2 films above 20 nm. ,, …”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] Fast switching (around 10 ns) has also been observed in ferroelectric ZrO 2 films. 31,32 It is commonly found that switching dynamics follows Nucleation Limited Switching (NLS) model, 33 as expected for polycrystalline films, contrary to the Kolmogorov-Avrami-Ishibashi (KAI) model 34,35 expected for films of high crystalline quality. 36 It has been reported that the increase of remanent polarization ascribed to the increase of non-pinned ferroelectric orthorhombic domains by doping or electric cycling is correlated with an increase of the characteristic switching time.…”
Section: Introductionmentioning
confidence: 99%
“…[121] HfO 2 -and ZrO 2 -based films exhibit rapid switching (in the nanosecond range). [122] Moreover, HZO films show good FE properties even at an ultralow thickness (≈1 nm), which is not the case for perovskite FE thin films. [123] Flexible HZO films can acquire FE properties up to 420 K and are suitable for flexible cooling devices.…”
Section: Zro 2 -And Hfo 2 -Based Materialsmentioning
confidence: 99%
“…[ 121 ] HfO 2 ‐ and ZrO 2 ‐based films exhibit rapid switching (in the nanosecond range). [ 122 ] Moreover, HZO films show good FE properties even at an ultralow thickness (≈1 nm), which is not the case for perovskite FE thin films. [ 123 ]…”
Section: Zro2‐and Hfo2‐based Materialsmentioning
confidence: 99%